Estimation of Slip Distribution of the 2007 Bengkulu Earthquake from GPS Observations Using the LeastSquares Inversion Method - Awaluddin, Moehammad; Meilano, Irwan; Widiyantoro, Sri (ITB Journal Publisher, LPPM ITB, 2012)
ContinuousÂ GlobalÂ PositioningÂ SystemÂ (GPS)Â observationsÂ showed significantÂ crustalÂ displacementsÂ asÂ aÂ resultÂ ofÂ theÂ BengkuluÂ earthquake occurring on September 12, 2007. A maximum horizontal displacement of 2.11 m was observed at PRKB station, while the vertical component at BSAT station was lifted up with a maximum of 0.73 m, and the vertical component at LAIS station had subsidedÂ â0.97 m. Adding more constraints on the inversion for the Bengkulu earthquake slip distribution inferred from GPS observations can help solveÂ theÂ underdeterminedÂ least-squaresÂ inversion.Â CheckerboardÂ testsÂ were performedÂ toÂ helpÂ conductÂ theÂ weightingÂ forÂ constrainingÂ theÂ inversion.Â The inversion calculation yielded an optimal value for the slip distribution by giving the smoothing constraint a weight of 0.001 and the slip constraint a weight of = 0 at the edge of the earthquake rupture area. The maximum co-seismic slip of the optimal inversion calculation was 5.12 m at the lower area of PRKB station and BSAT station. The seismic moment calculated from the optimal slip distribution was 7.14 x 1021 Nm, which is equivalent to a magnitude of 8.5.